Preparation method and application of carbonized polycrystalline phosphogypsum self-hardening particles

By adding alkaline materials to the phosphogypsum and granulation treatment, combined with autoclaving and CO2 carbonization treatment, carbonized polycrystalline phosphogypsum autohardened particles with high strength and low water absorption are prepared, which solves the problems of poor fluidity and easy agglomeration of phosphogypsum and expands its application scope.

CN119774907APending Publication Date: 2025-04-08YIDU XINGFA CHEMICAL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411881663.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-11-22
Filing Date
2024-12-19
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Phosphogypsum is poor in fluidity as a powder and is prone to agglomeration, affecting the effectiveness of industrial application.

Method used

By adding lime or calcium oxide-containing materials to the phosphogypsum for mixing, the pH is controlled between 10-11, the pelletization is carried out after the granulation and the CO2 carbonization is carried out, and finally curing is carried out to prepare carbonized polycrystalline phosphogypsum autohardened particles.

Benefits of technology

It improves the strength of phosphogypsum particles, reduces the water absorption rate, solves the problem of phosphogypsum being prone to agglomeration, and broadens its application in cement retarders and aggregates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774907A_ABST
    Figure CN119774907A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ardealite treatment, and particularly discloses a preparation method and application of carbonized polycrystalline ardealite self-hardening particles, the preparation method comprises the following steps: S1, adding lime or a material containing calcium oxide into ardealite, mixing, and controlling the pH to be 10-12; s2, granulating the ardealite obtained in the step S1, then carrying out autoclaved treatment, and then introducing CO2 for carbonization treatment; and finally, curing to obtain the carbonized polycrystalline ardealite self-hardening particles. On the basis of conventional ardealite granulation, steam curing and carbonization curing are provided, CO2 enters gaps after ardealite dehydration and is carbonized with excessive modification substances added during modification to generate calcium carbonate, the gaps are filled, carbonized polycrystalline ardealite self-hardening particles are obtained, the strength of the ardealite particles is improved, powder of the ardealite particles is reduced, and the strength of the ardealite particles is improved. The method can be applied to cement retarders or aggregates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of phosphogypsum utilization, and specifically relates to a preparation method and application of carbonized polycrystalline phosphogypsum self-hardening particles. Background Art

[0002] Phosphogypsum is an industrial solid waste residue produced in the process of preparing phosphoric acid by sulfuric acid method. Every ton of phosphoric acid produced produces 4 to 5 tons of phosphogypsum. The main components of phosphogypsum are calcium sulfate dihydrate, followed by silicon dioxide, and a small amount of phosphorus and fluorine. The output of phosphogypsum is large, and storage is the main disposal method. The storage of phosphogypsum occupies a large amount of land resources and is easy to cause water pollution. Phosphogypsum replaces natural gypsum as a cement retarder, which not only saves a lot of precious gypsum resources, but also turns waste into treasure with low cost. It has important environmental and economic significance and has become one of the main ways to comprehensively reuse phosphogypsum waste. However, phosphogypsum is powdery, has high water content, high viscosity, and poor fluidity. During the use process, large silos need to be set up to control the moisture, which is easy to cause problems such as silo blockage and agglomeration, affecting the effect of industrial application. Granulation of phosphogypsum can improve the use effect and broaden the use path. For example, after granulation, it can be used as a spherical cement retarder and can be used as aggregate in roadbed materials. In order to enhance the strength of the particles, cementitious materials can be added during the granulation process or the granulation can be dehydrated at medium or low temperature to become semi-hydrated phosphogypsum, and then activators, phosphogypsum impurity passivators, neutralizers, skeleton stabilizers and other materials can be added to the semi-hydrated phosphogypsum, and then after adding water, pressurizing and curing, water-resistant phosphogypsum products can be prepared for calcination.

[0003] CN113072318A discloses a spherical phosphogypsum and its preparation method and application. The phosphogypsum is mixed with cement and an improver and then granulated. Then, the phosphogypsum is slurried in cement slurry to coat the surface of the particles with a layer of cement slurry. Then, the particles are steam cured in an autoclave. The process requires cement to be used twice, which is costly. CN116283015A controls the phosphoric acid process, mixes fresh hemihydrate gypsum generated by wet phosphoric acid and dihydrate gypsum dry residue evenly, obtains twin crystalline phosphogypsum, and utilizes the gelling properties of the hemihydrate gypsum itself to make it self-harden during natural curing. However, this solution is limited by the phosphoric acid process. Summary of the invention

[0004] The present invention provides a preparation method and application of carbonized polycrystalline phosphogypsum self-hardening particles. The obtained phosphogypsum particles have high strength and can be used as cement retarder or aggregate.

[0005] The technical solution of the present invention is to provide a method for preparing carbonized polycrystalline phosphogypsum self-hardening particles, comprising the following steps: S1. Add lime or calcium oxide-containing materials to phosphogypsum and mix them to control the pH between 10 and 11; S2, granulating the phosphogypsum obtained in S1, and then autoclaving it, and then introducing CO2 to carbonize it; and finally curing it to obtain carbonized polycrystalline phosphogypsum self-hardening particles.

[0006] In some embodiments, during the modification in S1, lime or carbide slag is added for mixing.

[0007] In some embodiments, during granulation in S2, a binder of 0.5-1% by mass of phosphogypsum is added.

[0008] In some embodiments, the binder is one or more of hydroxy-terminated polybutadiene, sodium carboxymethyl cellulose, clay, and bentonite.

[0009] In some embodiments, the diameter of the particles after granulation is 10-20 mm.

[0010] In some embodiments, during the autoclave treatment in S2, the autoclave temperature is 140-160° C., the autoclave pressure is 0.5-0.7 MPa, and the autoclave time is 90-120 min.

[0011] In some embodiments, after the autoclave is completed in S2, the steam is stopped and the temperature is lowered, and CO2 is introduced until the autoclave temperature drops below 55°C and then stopped.

[0012] In some embodiments, the CO2 inlet flow rate is 3-6 L / min.

[0013] The invention also relates to carbonized polycrystalline phosphogypsum self-hardening particles prepared by the method.

[0014] The invention also relates to the application of carbonized polycrystalline phosphogypsum self-hardening particles prepared by the method in cement retarders and aggregates.

[0015] The present invention has the following beneficial effects: When treating phosphogypsum, the present invention first adds an alkaline material to adjust the pH value for modification, solidifies the water-soluble impurities in the phosphogypsum, and then performs granulation and molding, thereby solving the problem that the phosphogypsum as a powder has poor fluidity and is easy to agglomerate during use; and through autoclaving and curing, most of the crystal water and free water are removed to obtain polycrystalline phosphogypsum containing hemihydrate and dihydrate, which has a porous structure, and then carbon dioxide is introduced to enter the gaps of the dehydrated phosphogypsum, react with the excess alkaline material added for modification, generate calcium carbonate, fill the gaps, and obtain carbonized polycrystalline phosphogypsum particles, which can reduce the water absorption rate and improve the particle strength at the same time.

[0016] The present invention can realize the resource utilization of phosphogypsum and CO2, effectively alleviate the environmental problems caused by phosphogypsum and CO2, and create economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A process flow chart of the method is provided for the present invention. DETAILED DESCRIPTION

[0018] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0019] The phosphogypsum used in the following examples and comparative examples was obtained from a phosphorus chemical enterprise, and its composition is shown in Table 1 below.

[0020] Table 1

[0021] Example 1 The treatment process of phosphogypsum is as follows Figure 1 As shown, 10wt% carbide slag is added to phosphogypsum, and the pH value is 11.06; 1% of the binder bentonite is added to the modified phosphogypsum and mixed, and granulated in a granulator, with a particle size of about 10-20mm; the particles are placed in an autoclave, autoclaved at 140°C for 90 minutes, and the introduction of water vapor is stopped; CO2 is introduced into the autoclave at a flow rate of 5L / min, and ventilation is stopped when the temperature is lower than 55°C; and it is naturally cooled in the air.

[0022] The obtained carbonized polycrystalline phosphogypsum particles had a balling rate of 92.1%, strength of 82N on the first day, 118N on the third day, 176N on the fifth day, pH value of 9.21, and no water-soluble phosphorus and water-soluble fluorine were detected.

[0023] Example 2 The method steps are the same as those in Example 1, except that 8% carbide slag is added and the pH value is 10.15; the modified phosphogypsum is mixed with 1% bentonite as a binder and granulated in a granulator to a particle size of about 10-20 mm; the particles are placed in an autoclave and autoclaved at 140°C for 90 minutes, and the introduction of water vapor is stopped; CO2 is introduced into the autoclave at a flow rate of 5 L / min, and ventilation is stopped when the temperature is lower than 55°C; and the mixture is naturally cooled in the air.

[0024] The obtained carbonized polycrystalline phosphogypsum particles had a balling rate of 91.5%, strength of 57N on the first day, 95N on the third day, 123N on the fifth day, pH value of 8.45, and no water-soluble phosphorus and water-soluble fluorine were detected.

[0025] Example 3 The method steps are the same as those in Example 1, except that 10% carbide slag is added and the pH value is 11.21; 5‰ of a binder, sodium carboxymethyl cellulose, is added to the modified phosphogypsum and mixed, and granulated in a granulator to a particle size of about 10-20 mm; the particles are placed in an autoclave and autoclaved at 140°C for 90 minutes, and the introduction of water vapor is stopped; CO2 is introduced into the autoclave at a flow rate of 5 L / min, and ventilation is stopped when the temperature is lower than 55°C; and the mixture is naturally cooled in the air.

[0026] The obtained carbonized polycrystalline phosphogypsum particles had a balling rate of 82.3%, strength of 75N on the first day, 112N on the third day, 165N on the fifth day, pH value of 9.32, and no water-soluble phosphorus and water-soluble fluorine were detected.

[0027] Example 4 The method steps are the same as those in Example 1, except that 10% carbide slag is added to the phosphogypsum, and the pH value is 11.15; 1% of the binder bentonite is added to the modified phosphogypsum, and the mixture is granulated in a granulator, and the particle size is about 10-20 mm; the particles are placed in an autoclave, autoclaved at 140°C for 120 minutes, and the introduction of water vapor is stopped; CO2 is introduced into the autoclave at a flow rate of 5L / min, and ventilation is stopped when the temperature is lower than 55°C; and the mixture is naturally cooled in the air.

[0028] The obtained carbonized polycrystalline phosphogypsum particles had a ball formation rate of 92.1%, a strength of 90N on the first day, 124N on the third day, 185N on the fifth day, a pH value of 8.95, and undetectable water-soluble phosphorus and water-soluble fluorine contents.

[0029] Example 5 The method steps are the same as those in Example 1, except that 10% carbide slag is added to the phosphogypsum, and the pH value is 11.27; 1% of a binder is added to the modified phosphogypsum and mixed, and granulated in a granulator, with a particle size of about 10-20 mm; the particles are placed in an autoclave, autoclaved at 150°C for 90 minutes, and the introduction of water vapor is stopped; CO2 is introduced into the autoclave at a flow rate of 5 L / min, and ventilation is stopped when the temperature is lower than 55°C; and the mixture is naturally cooled in the air.

[0030] The obtained carbonized polycrystalline phosphogypsum particles had a balling rate of 92.1%, strength of 92N on the first day, 135N on the third day, 201N on the fifth day, pH value of 8.72, and no water-soluble phosphorus and water-soluble fluorine were detected.

[0031] Example 6 The method steps are the same as those in Example 1, except that 10% carbide slag is added to the phosphogypsum, and the pH value is 11.06; 1% of a binder is added to the modified phosphogypsum and mixed, and granulated in a granulator, with a particle size of about 10-20 mm; the particles are placed in an autoclave, autoclaved at 150°C for 120 minutes, and the introduction of water vapor is stopped; CO2 is introduced into the autoclave at a flow rate of 5L / min, and ventilation is stopped when the temperature is lower than 55°C; and the mixture is naturally cooled in the air.

[0032] The obtained carbonized polycrystalline phosphogypsum particles had a balling rate of 92.1%, a strength of 90N on the first day, 132N on the third day, 198N on the fifth day, a pH value of 8.65, and water-soluble phosphorus and water-soluble fluorine contents of 0.

[0033] Example 7 The method steps are the same as those in Example 1, except that 10% carbide slag is added to the phosphogypsum, and the pH value is 11.06; 1% of a binder is added to the modified phosphogypsum and mixed, and granulated in a granulator, with a particle size of about 10-20 mm; the particles are placed in an autoclave, autoclaved at 140°C for 90 minutes, and the introduction of water vapor is stopped; CO2 is introduced into the autoclave at a flow rate of 3L / min, and ventilation is stopped when the temperature is lower than 55°C; and the mixture is naturally cooled in the air.

[0034] The obtained carbonized polycrystalline phosphogypsum particles had a ball formation rate of 92.1%, a strength of 57N on the first day, 98N on the third day, 145N on the fifth day, a pH value of 10.21, and no water-soluble phosphorus and water-soluble fluorine were detected.

[0035] Example 8 The method steps are the same as those in Example 1, except that 10% carbide slag is added to the phosphogypsum, and the pH value is 11.06; 1% of a binder is added to the modified phosphogypsum and mixed, and granulated in a granulator, with a particle size of about 10-20 mm; the particles are placed in an autoclave, autoclaved at 140°C for 90 minutes, and the introduction of water vapor is stopped; CO2 is introduced into the autoclave at a flow rate of 6 L / min, and ventilation is stopped when the temperature is lower than 55°C; and the mixture is naturally cooled in the air.

[0036] The obtained carbonized polycrystalline phosphogypsum particles had a balling rate of 92.1%, strength of 82N on the first day, 118N on the third day, 176N on the fifth day, pH value of 8.65, and no water-soluble phosphorus and water-soluble fluorine were detected.

[0037] Example 9 The method steps are the same as those in Example 1, except that 8% lime is added to the phosphogypsum, and the pH value is 11.27; 1% binder is added to the modified phosphogypsum and mixed, and granulated in a granulator, with a particle size of about 10-20 mm; the particles are placed in an autoclave, autoclaved at 140°C for 90 minutes, and the introduction of water vapor is stopped; CO2 is introduced into the autoclave at a flow rate of 5L / min, and ventilation is stopped when the temperature is lower than 55°C; and the mixture is naturally cooled in the air.

[0038] The obtained carbonized polycrystalline phosphogypsum particles had a balling rate of 92.5%, strength of 87N on the first day, 114N on the third day, 182N on the fifth day, pH value of 9.28, and no water-soluble phosphorus and water-soluble fluorine were detected.

[0039] Comparative Example 1: 10% carbide slag is added to phosphogypsum, and the pH value is 11.12; 1% of the binder bentonite is added to the modified phosphogypsum, and granulated in a granulator, with a particle size of about 10-20mm; the particles are placed in an autoclave, autoclaved at 140°C for 90 minutes, the water vapor is stopped, and naturally cooled in the air.

[0040] The obtained carbonized polycrystalline phosphogypsum particles had a balling rate of 92.1%, strength of 32N on the first day, 57N on the third day, 85N on the fifth day, a pH value of 10.57, and no water-soluble phosphorus and water-soluble fluorine were detected.

[0041] Comparative Example 2: 10% carbide slag is added to phosphogypsum, and the pH value is 11.06; 1% binder is added to the modified phosphogypsum and mixed, and granulated in a granulator, with a particle size of about 10-20mm; the particles are placed in an autoclave, the temperature in the autoclave is set to 55°C, CO2 is introduced into the autoclave at a flow rate of 5L / min, the carbonization time is 30 minutes, and naturally cooled in the air.

[0042] The obtained carbonized polycrystalline phosphogypsum particles had a balling rate of 92.1%, a strength of 24N on the first day, 42N on the third day, 53N on the fifth day, a pH value of 10.35, and no water-soluble phosphorus and water-soluble fluorine were detected.

[0043] It can be seen from Comparative Example 1 and Comparative Example 1 that the strength of the phosphogypsum particles can be enhanced by carbonization curing; it can be seen from Comparative Example 1 and Comparative Example 2 that the strength of the phosphogypsum particles cannot be improved by carbonization alone without undergoing the autoclaving process; it can be seen from Comparative Example 1 and Example 2 that the higher the content of alkaline substances in the modification process, the higher the particle strength; it can be seen from Comparative Example 1 and Example 3 that the longer the autoclaving time, the higher the strength of the phosphogypsum particles.

[0044] The above embodiments describe the preferred implementation of the present invention, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing carbonized polycrystalline phosphogypsum self-hardening particles, characterized in that: The following steps are involved: S1. Add lime or calcium oxide-containing materials to phosphogypsum and mix them to control the pH between 11 and 12; S2, granulating the phosphogypsum obtained in S1, and then autoclaving it, and then introducing CO2 to carbonize it; and finally curing it to obtain carbonized polycrystalline phosphogypsum self-hardening particles.

2. The method according to claim 1, characterized in that: When modifying S1, lime or carbide slag is added for mixing.

3. The method according to claim 1, characterized in that: When granulating in S2, a binder of 0.5-1% by mass of phosphogypsum is added.

4. The method according to claim 3, characterized in that: The binder is one or more of terminal hydroxyl polybutadiene, sodium carboxymethyl cellulose, clay or bentonite.

5. The method according to any one of claims 1 to 4, characterized in that: The diameter of the particles after granulation is 10-20 mm.

6. The method according to claim 1, characterized in that: During the autoclave treatment in S2, the autoclave temperature is 140-160° C., the autoclave pressure is 0.5-0.7 MPa, and the autoclave time is 90-120 min.

7. The method according to claim 1, characterized in that: After the autoclave in S2 is completed, the steam is stopped and the temperature is lowered, and CO2 is introduced until the autoclave temperature drops below 55°C and then stopped.

8. The method according to claim 7, characterized in that: The CO2 inlet flow rate is 3-6L / min.

9. Carbonized polycrystalline phosphogypsum self-hardening particles prepared by the method according to any one of claims 1 to 8.

10. Use of the carbonized polycrystalline phosphogypsum self-hardening particles prepared by the method according to any one of claims 1 to 8 in cement retarders or aggregates.

Citation Information

Patent Citations

  • Spherical phosphogypsum as well as preparation method and application thereof

    CN113072318A

  • Method for preparing self-hardening spherical cement retarder by using bicrystal phosphogypsum

    CN116283015A